a ANALISIS STRUKTUR EKONOMI DAN IDENTIFIKASI SEKTOR UNGGULAN DI KABUPATEN BERAU PERIODE 2001-2017 - Bustan, Riza (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2019)
ABSTRACT The economy of Berau Regency undergoes changes in the structure dominated by the primary sector through: mining & excavation and agriculture, forestry & fisheries. Changes in the contribution of the secondary sector towards the tertiary sector are dominated by the large & retail trade sector; transportation & warehousing; and education services. Changes in the secondary sector experienced a slowdown sourced from the processing industry giving a slow Shift-Share and the construction sector being the biggest driver for changes in the secondary sector. The results of the Location Quotient analysis for the period 2001-2017 state that the business sectors categorized as superior in Berau Regency include the mining & quarrying sector; agriculture, forestry & fisheries; big & retail trade; transportation & warehousing; education services; government administration; real estate; food & drink accommodation providers; information & communication; other services; health services & social activities; company services; water supply; and the electricity & gas procurement sector.   Keywords: Superior Economic and Sector Structure   ABSTRAK           Perekonomian Kabupaten Berau mengalami perubahan struktur yang didominasi sektor primer melalui: pertambangan & penggalian dan pertanian, kehutanan & perikanan. Perubahan kontribusi sektor sekunder menuju sektor tersier didominasi sektor perdagangan besar & eceran; transportasi & pergudangan; dan jasa pendidikan. Perubahan sektor sekunder mengalami perlambatan bersumber dari industri pengolahan memberikan Shift-Share yang lambat dan sektor konstruksi menjadi pemotor terbesar bagi perubahan sektor sekunder.           Hasil analisis Location Quotient periode 2001-2017 menyatakan lapangan usaha dikategorikan unggulan di Kabupaten Berau meliputi sektor pertambangan & penggalian; pertanian, kehutanan & perikanan; perdagangan besar & eceran; transportasi & pergudangan; jasa pendidikan; administrasi pemerintahan; real estate; penyedia akomodasi makan & minum; infromasi & komunikasi; jasa lainnya; jasa kesehatan & kegiatan sosial; jasa perusahan; pengadaan air; dan sektor pengadaan listrik & gas.   Kata Kunci : Struktur Ekonomi dan Sektor Unggulan